Book Review: Bates, R.H. 2017: The Development Dilemma: Security, Prosperity, and a Return to History. (October 2018) - Ahmed, Iqbal
Bates, R.H. 2017: The Development Dilemma: Security, Prosperity, and a Return to History . Princeton, NJ and Oxford: Princeton University Press. 200 pp. £22.95 (Hardback). ISBN-10: 0691167354. £18.04 (e-book). ISBN-13: 978-0691167350.